Incorporating quinoxaline unit as additional acceptor for constructing efficient donor-free solar cell sensitizers. (February 2018) - Shen, Chao; Wu, Yongzhen; Zhang, Weiwei; Jiang, Huiyun; Zhang, Hao; Li, Erpeng; Chen, Bingxu; Duan, Xuezhi; Zhu, Wei-Hong
Abstract: Donor-free organic dyes that do not contain typical arylamine groups have been recently recognized as a new model for designing efficient photosensitizers for application in dye-sensitized solar cells. Until now, the most efficient donor-free sensitizers are composed of oligo-thiophenes or covalently connected cyclopentadithiophene (CPDT) units with one terminal of cyanoacetic acid as the anchoring group. In this paper, we propose a new strategy for improving the performance of CPDT based donor-free dyes by incorporating an electron-deficient quinoxaline unit into the π-chain. Three new donor-free dyes ofSC1-3 with main difference of number and location of long alkyl chains are designed and synthesized. The incorporated electron-deficient quinoxaline unit is found to enhance the intramolecular charge transfer transition and weaken the deprotonation effect on absorption properties, resulting in an improved light harvesting efficiency relative to the reference dyeCPDT-3 . The influence of long alkyl chains on the optical and electronic properties as well as photovoltaic performance is systematically studied. When applied in iodide-triiodide electrolyte based DSSCs, the best performing quinoxaline based donor-free dyeSC-1 shows a power conversion efficiency (PCE) of 8.05%, which is 20% higher than that of reported donor-free dyeCPDT-3 (PCE of 6.7%). Highlights: Three new donor-free dyes based on CPDT units have been synthesized. The quinoxaline unit is incorporated into the CPDT chain as additional acceptor. The influence of long alkyl chains is systematically studied. The best performing sensitizerSC-1 shows a highest PCE of 8.05%.